Heavy metals in waters used for human consumption and crop irrigation - Silva, Laercio Santos [UNESP]; Galindo, Izabel Cristina De Luna; Do Nascimento, Clístenes Wilians Araújo; Gomes, Romário Pimenta [UNESP]; De Freitas, Ludmila [UNESP]; De Oliveira, Ivanildo Amorim [UNESP]; Campos, Milton César Costa; Da Cunha, José Maurício (Instituto de Pesquisas Ambientais em Bacias Hidrograficas (IPABHi), 2018)
The consumption of contaminated water is a major source of heavy metal contamination in humans and animals. This study therefore aimed to assess Cd, Cu, Mn, Ni, Pb, and Zn levels in water used for human and animal consumption and vegetable crop irrigation in Camocim de São Félix, Pernambuco, Brazil. Water samples were collected on the studied farms from an artesian well and reservoirs used for human and animal consumption as well as for crop irrigation. The results showed that concentrations of Cd (> 0.001 mg L-1), Ni (> 0.025 mg L-1) and Pb (> 0.01 mg L-1) were above the maximum allowable limits established under Brazilian law, indicating the need for a preventive monitoring program and immediate intervention initiatives aimed at the sources of contamination. The results demonstrate the need to quantify heavy metal content in vegetable crops, since their contamination by irrigation water may make them harmful to human health. Rainfall has a seasonal effect on heavy metal concentrations in water, showing a significant effect on Pb levels, whereas Cd and Ni content was less dependent on seasonal variation.
Metais pesados em águas utilizadas para consumo humano e irrigação de culturas
Keywords: Agrochemicals; Cadmium; Diffuse pollution; Lead; Trace elements